Analisis Bagi Hasil (Mukhabarah) Antara Petani Penggarap dan Pemilik Lahan pada Pertanian Jagung di Desa Bullisu Kabupaten Pinrang - Aini Yasih Darwin; Mardia; Desy Arum Sunarta (CV. ALIM'SPUBLISHING, 2023)
Mukhabarah is a form of cooperation in agriculture, which is a form of cooperation between sharecroppers and landowners, where the land owner gives his land to the manager or sharecropper to be managed or planted and maintained based on an agreement (contract) in exchange for a certain part (percentage) of the land. yields. Mukhabarah also occurred in Bulisu Village, Pinrang Regency, where the community was more familiar with the term profit sharing. The profit-sharing collaboration that takes place in Bulisu Village, Pinrang Regency is generally a contract only orally based on trust without presenting witnesses, and the contract period is not clearly defined. The purpose of this research is to find out what the profit sharing system in Bulisu Village looks like and whether it is in accordance with the profit sharing system (mukhabarah). This study uses qualitative research with a perspective approach to data collection through observation, interviews, and documentation. The results of the study indicate that the cooperation system that occurs is a profit-sharing system. The implementation of the profit-sharing system in Bulisu Village is a mukhabarah contract in Islamic economics, but there are some things that are not quite right, namely the contract period that is not clearly defined, so that the practice is not fully in accordance with the Islamic concept. determined